Possibilities of the Subject ‘Information and Communication Technologies’ in Accustoming Primary School Students to Research Activities - Tashkenbayevna, Nazgul; Kenesbaev, Serik M.; Zhailauova, M.K.; Elmira, Uaidullakyzy; Nurzhanova, S. A.; Stambekova, A. S. (International journal of interactive mobile technologies, 2018)
This article considers the issue of accustoming primary school students to research activities and basically focuses on information technology, which is the main tool for increasing cognitive activity. We define joint creative activities of teacher and student, which are carried out in seeking the solution of the unknown problem defined as an academic goal of students, and as a result of which cultural values are passed on as research activities. In this case, the teacher acts as the organiser of the forms and situations of research activity. It is insufficient for school children just to make a decision in solving the problems occurring in academic goals, the results achieved in the implementation process should be helpful for someone. From this point of view, the issue of molding a motivation, which permanently leads the student to master study-research skills, will be on the agenda.